Impacts of conservation incentives in protected areas: The case of Bolsa Floresta, Brazil - Cisneros, E.; Borner, J.; Pagiola, S.; Wunder, Sven (Elsevier, 2022)
Conditional incentives are a promising complementary approach to conserve tropical forests, for example, in multiple-use protected areas. In this paper we analyze the environmental impacts of Bolsa Floresta, a forest conservation program that combines direct conditional payments with livelihood-focused investments in 15 multiple-use reserves in the Brazilian state of Amazonas. We use grid-based data, nearest-neighbor matching, and panel data econometrics to compare three forest-related program outcomes – deforestation, degradation, and fires – of participating and non-participating reserve areas. Forest threats were low before and after treatment, because the program prioritized low-pressure sites. Thus, we find significant but small additional conservation effects from the implementation of the program. Notwithstanding, treatment effects are relatively larger in areas with higher deforestation pressure and higher potential agricultural income. Our findings add to the growing body of evidence showing that adverse spatial targeting of conservation incentives, i.e. disproportionally enrolling low–pressure sites, is a prime cause for the low additionality found in rigorous impact evaluations of many existing initiatives.